Numerical modeling of three-dimensional non-stationary flows and heat/mass transfer in a cylindrical liquid bridge in the absence of gravity - Lyubimova, Tatyana Petrovna; Skuridin, Robert Vladislavovich (Computational Continuum Mechanics, 2010)
Numerical modeling of temperature distribution, velocity fields and dopant concentration (Si:P) during silicon crystal growth by the floating zone method under microgravity conditions is carried out. The non-stationary three-dimensional problem is solved using the finite difference method. The deformations of a liquid bridge free surface and crystallization and melting fronts are neglected. The simulation shows both the establishment of stationary axisymmetric modes and the development of non-stationary three-dimensional flow modes.
Keywords: convective flows; liquid zone; numerical modeling; finite difference method